The Contemporary Cinema / With thirty-two plates - Houston Penelope (Penguin Books, 1963)
Preface, Introductory, The Italian Experience, Which Picture Made the Money, The Nervous Years, Production Values, Taken From the French, The Free French, Room at the Top, Thought Control. The Major Industries, The Movie-Makers, Looking for an Audience, Towards a New Cinema, Check-List of Films and Directors, Selected Book List, Index.
Preface, Introductory, The Italian Experience, Which Picture Made the Money, The Nervous Years, Production Values, Taken From the French, The Free French, Room at the Top, Thought Control. The Major Industries, The Movie-Makers, Looking for an Audience, Towards a New Cinema, Check-List of Films and Directors, Selected Book List, Index.